2004
DOI: 10.1016/j.ejcts.2003.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical application of human fibrinogen/thrombin-coated collagen patch (TachoComb) for treatment of air leakage after standard lobectomy

Abstract: TC could be proven as well-tolerated and safe. In the subgroup of patients with established air leakage, TC showed superior potential in reduction of intra-operative air leakage as well as in reduction of intensity and duration of postoperative air leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 20 publications
0
65
0
1
Order By: Relevance
“…Nearly all of these studies represent a heterogeneous group of trials with a variety of products [16][17][18]. An overall review of these trials concluded that systematic use of these products were not recommended, as only one trial demonstrated a reduction in the duration or incidence of prolonged air leak [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all of these studies represent a heterogeneous group of trials with a variety of products [16][17][18]. An overall review of these trials concluded that systematic use of these products were not recommended, as only one trial demonstrated a reduction in the duration or incidence of prolonged air leak [13].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining apnoea with stand-still but inflated lung (end inspiratory) at critical junctures further aided surgery. Prolonged parenchymal air leak is the most common complication after lung resection (48-70% patients) [14] and we managed to reduce this using our ventilatory manoeuvres. Prolonged chest tube drainage, pain and immobilization, infections and broncho-pleural fistulae and prolonged hospital stay are the repercussions of prolonged air leak.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Comparator products such as FloSeal, 12,13 Quixil 14,15 and Beriplast P 16,17 are supported by evidence in other areas of surgery, but TachoSil ® is the only product supported by randomised controlled trials in the kidney surgery setting. Randomised controlled trials have also shown the effectiveness of TachoSil ® in liver 7 and lung 18 surgery. In addition, a prospective observational cost-benefit analysis of the impact of the use of TachoSil ® in a variety of surgical settings on operating time, length of hospital stay, transfusions required, and resource use was performed in 185 centres in Germany.…”
Section: Discussionmentioning
confidence: 99%